FACTORS INFLUENCING THE OCCURRENCE OF PENDING INPATIENT CLAIMS IN HOSPITALS - Windy Suganda; Anastasya Shinta Yuliana; Anastasya Shinta Yuliana, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Social Security is a form of social protection that allows everyone to meet their basic life needs. Social security includes all social welfare efforts aimed at improving the quality of human life and overcoming backwardness, dependency, neglect and poverty. One form of social health security in Indonesia is the social security violation agency or commonly known as BPJS. In the implementation of the use of BPJS Health, claims will be made, which will be carried out after the patient has completed treatment, in the process of submitting claims from the Hospital to BPJS Health with several stages of verifying the completeness of files both in terms of membership administration, service administration and health service verification. The aim of this research is to determine the factors that influence pending claims for inpatient care at home. Pending claims that occur are caused by several factors, namely, inappropriate or incomplete filling in of items in the patient's medical record, such as a mismatch between the diagnosis and the medical resume, then the therapy given does not match the existing diagnosis that has been made by the patient. doctor in charge of the patient (DPJP). This research is descriptive qualitative in nature, which was carried out at the hospital from April 2024 to May 2024. Data collection was carried out by interviewing several related informants and from secondary data in the form of recapitulation data of pending inpatient treatment. Based on the results obtained from secondary data in the form of recapitulation data for pending inpatient care and the results of interviews with several informants in the casemix unit, it was found that there were factors causing claims for pending inpatient care at the hospital, one of which was incomplete patient administration files. This is also supported by data from interviews conducted with 5 informants in the casemix unit, 1 inpatient cashier, and 2 nurses, as well as observations made which showed that there were still several patient administration files that were incomplete, where assembling was always coordinate with the relevant service unit and search for and complete incomplete files in the medical record. Keywords: pending claims, BPJS claims, BPJS inpatient care